CONSISTENCY OF INDONESIA'S INTERNATIONAL TREATY IMPLEMENTATION IN THE FIELD OF INVESTMENT IN THE NATIONAL LEGAL SYSTEM: A POLITICAL PERSPECTIVE OF LAW TO REALIZE COMMUNITY WELFARE - Arief, Eva (UNTAG Law Review, 2023)
This research examines the issue of consistency in the implementation of Indonesia's international agreements in the field of investment in Indonesia's national legal system, with a focus on achieving public welfare. The political implementation of Indonesian International Treaties in the field of investment into national law is divided into two periods. The period before the Constitutional Court Decision Number 13/PUU-XVI/2018 and the subsequent period. The court decision mainly talks about how to ratify an international treaty. Article 2 of Law No. 24/2000 on International Agreements states that ratification of international agreements is done in two ways, namely ratification by passing a law by the Parliament and ratification by issuing a presidential regulation by the President. Ratification through parliament if an international agreement has a broad and fundamental impact on the livelihood of the people related to the financial burden of the state and or requires amendments to the law as stipulated in article 11 paragraph (2) of the 1945 Constitution. Meanwhile, the position of international agreements in the field of investment, based on Article 11 (2), the ratification of International Agreements is based on Presidential Regulations. At the same time, there are international investment agreements whose material can have a broad and fundamental impact on people's lives, so the absence of parliamentary control can lead to inequality and potential negative impacts on people's welfare. Through normative legal research methods, the findings show that foreign investment must provide the maximum benefit for economic development and public welfare, and the ratification of international investment agreements can be done either through presidential regulations or legislation by passing a law